Efek intensitas latihan beban tubuh terhadap penurunan indeks massa tubuh (BMI) pada mahasiswa. - Dwijayanti, Karlina; Nugroho, Untung; Rumpoko, Satrio Sakti; Muryadi, Agustanico Dwi; Sari, Yudi Karisma (Universitas Nusantara PGRI Kediri, 2023)
Obesity in adolescents is very prone to occur due to consumption of fast food, sweet food/drink patterns, likes to play games without knowing the time, and low physical activity. Overnutrition in adolescents is characterized by relatively excessive body weight. The nutritional needs of adolescents are very important, for example, the needs of athletes, so an appropriate training model is needed. Physical activity can burn fat in the body, thereby increasing the body's metabolism. Bodyweight workout is a form of physical activity to maintain body weight. This study aimed to determine the effect of bodyweight workouts on reducing BMI. The study subjects used the Proportionate stratified random sampling technique by taking a sample of 35 male and female university students with a body mass index above 25. The research instrument uses body mass index (BMI) measurements. The data analysis technique used prerequisite tests for normality, homogeneity, and data analysis using SPSS 25. The decreased results were obtained from an average BMI of 27.411 to 25.086, 2.326 or 8.486%. This study concludes the importance of doing bodyweight workouts to reduce BMI in college students.